Investigation of weight management-related focus areas in middle-class overweight/obese Black (Zulu) women to advise healthy weight loss intervention development - Kassier, Susanna Maria (Division of Human Nutrition, 2015)
The South African Demographic and Health Survey (1998 and 2003) revealed that urban black women had the highest prevalence of overweight/obesity and central obesity across all population and gender groups. This trend was confirmed by the South African National Health and Nutrition Examination Survey (SANHANES-1) who reported a substantial increase in the prevalence of obesity among black South African women. Hence, the high prevalence of overweight/obesity and central obesity among urban black South African women needs to be addressed through targeted weight loss/management interventions, as obesity and central obesity are risk factors for the development of a number of non-communicable diseases (NCDs). However, from the international literature, it is evident that overweight/obese black women are less likely to embark on a weight loss intervention, while those who seek treatment, are unlikely to complete the intervention, as weight loss interventions targeting as well as including black women have reported attrition rates ranging from 0to 79%. In addition, at this point in time, no common attrition tendencies have been documented for large clinic-based weight loss interventions targeting African-American women in the United States of America. As there is a serious paucity of published information on weight loss interventions targeting overweight/obesity in urban black South African women, the aim of this research was to investigate weight management-related focus areas in overweight/obese black (Zulu) women residing in an urban area in South Africa. This information is essential to advise the development of healthy weight loss interventions and appropriate messaging to promote weight loss and maintenance in black South African women. In order to achieve the this aim, the following research questions were formulated: (i) What is the weight management related profile of overweight/obese treatment-seeking black women; (ii) What is the outcome of a culturally sensitive healthy weight loss intervention in terms of weight loss, compliance (attendance of intervention sessions, lifestyle changes) and attrition: and (iii) Which factors may explain the outcomes of the culturally sensitive healthy weight loss intervention? To guide the investigation of these research questions the researcher first set out to identify weight management-related focus areas for overweight/obese black women from the literature. Ten succinct focus areas emerged and include the following: 1) treatment seeking behaviour; 2) weight loss success; 3) compliance to and attrition from weight loss programmes; 4) cultural influences on body shape and size perception and satisfaction; 5) cultural influences on food choices and eating patterns6) cultural influences on physical activity; 7) environmental factors and social support; 8)appropriateness of the weight loss programme for the target population; 9) dietary restraint, disinhibition, perceived hunger and bingeing and 10) psychological well-being (depression).